Identification of jumping activity in volleyball by using accelerometer - Mok, K. M.; Jarning, J. M.; Hansen, B. H.; Bahr, R. (British Journal of Sports Medicine, 2014)
Background: In volleyball, training and match exposure is a risk factor for developing patellar tendinopathy which is known as jumper's knee. The frequency of jumping is an indicator of the intensity of jumping activity in training and match. Accelerometer provides measure of time-variant vertical acceleration which can potentially be transformed to the frequency of jumping activity. However, the ability of identifying jumping activity from other volleyball specific activity is unknown. Objective: To investigate the feasibility of using accelerometer to identify jumping activity from non-jumping activity in volleyball. Design: A methodological study.Setting Subjects performed 7 different volleyball specific activities including non-jumping (side stepping, diving and sprinting) and jumping (float serving, block jumping, jump serving and spike jumping). The time-variant vertical acceleration was recorded by a hip-worn accelerometer (ActiGraph GT3X+) with 100Hz sampling rate. Participants: Male elite volleyball players in national level (n=12). Risk factor assessment: Not applicable.Main outcome measurements The peak vertical acceleration of activities was extracted from the time-variant vertical acceleration data. One way ANOVA was run to assess whether the peak vertical acceleration differentiated by activity. Post-hoc analyses were carried out using pairwise comparisons with alpha (0.05) adjusted using the Bonferroni correction. Results: Not all the peak vertical accelerations for jumping activities were significantly different from those for non-jumping activities. Moreover, the variation of peak vertical acceleration between subjects was large.Results from ANOVA with post-hoc Bonferroni on peak vertical acceleration (g). Conclusions: Based on the measure of peak vertical acceleration from accelerometer, the non-jumping and jumping activity in volleyball cannot be distinguished. An alternative approach is needed for applying accelerometers to measure the frequency of jumping in volleyball?